Bucht mit Missionsstation Okak, Labrador (1900)
Color postcard providng an aerial view of Okak, Labrador. Shows Moravian mission station, possibly early twentieth century. Color postcard providng an aerial view of Okak, Labrador. Shows Moravian mission station, possibly early twentieth century.